Multikulturalisme Beragama Masyarakat Gunung Wungkal Pati Jawa Tengah - Mas'udi, Mas'udi (FIKRAH, 2019)
This article aims to analyze the dynamically religious multiculturalisme as it runs among the People of Gunungwungkal Region, District of Pati, Jawa Tengah Province. This research stands on thesis of the dynamic of people tolerances between their religious activities as it comes forward at the tradition of Selametan. Selametan is kind of acvities by praying with God on all of His mercies and blessings. This research designed by anthropological analysis as collect the data by interview, documentation, and participation. The data processing by ethnography with structural-functionalism theory. In the multiculturalism of Gunungwungkal peoples covered with their tolerance on social-culture and social-religious activities. The peoples of Gunungwungkal Region united their solidarities on cultural traditions, a like Selametan, Pesta Panen, Sedekah Bumi, Megengan, and Malam Satu Suro. All peoples active to get send and pray of God to give all his mercies and blessing with their ancestors.